A research and development (R&D) roadmap for broadly protective coronavirus vaccines: A pandemic preparedness strategy - Moore, Kristine A.; Leighton, Tabitha; Ostrowsky, Julia T.; Anderson, Cory J.; Danila, Richard N.; Ulrich, Angela K.; Lackritz, Eve M.; Mehr, Angela J.; Baric, Ralph S.; Baylor, Norman W.; Gellin, Bruce G.; Gordon, Jennifer L.; et al. (Vaccine, 2023)
Broadly protective coronavirus vaccines are an important tool for protecting against future SARS-CoV-2 variants and could play a critical role in mitigating the impact of future outbreaks or pandemics caused by novel coronaviruses. The Coronavirus Vaccines Research and Development (R&D) Roadmap (CVR) is aimed at promoting the development of such vaccines. The CVR, funded by the Bill & Melinda Gates Foundation and The Rockefeller Foundation, was generated through a collaborative and iterative process, which was led by the Center for Infectious Disease Research and Policy (CIDRAP) at the University of Minnesota and involved 50 international subject matter experts and recognized leaders in the field. This report summarizes the major issues and areas of research outlined in the CVR and identifies high-priority milestones. The CVR covers a 6-year timeframe and is organized into five topic areas: virology, immunology, vaccinology, animal and human infection models, and policy and finance. Included in each topic area are key barriers, gaps, strategic goals, milestones, and additional R&D priorities. The roadmap includes 20 goals and 86 R&D milestones, 26 of which are ranked as high priority. By identifying key issues, and milestones for addressing them, the CVR provides a framework to guide funding and research campaigns that promote the development of broadly protective coronavirus vaccines.